Multi-omics characterization of oncosis in spinal cord injury - Zhipeng Jiang; Youwei Guo; Zihan Wang; Jinhao Ouyang; Hailong Huang; Haoxuan Huang; Tianqian Shen; Lei Wang; Wen Yin; Xingjun Jiang; Caiping Ren (Neurobiology of Disease)
Spinal cord injury (SCI) initiates a cascade of complex secondary damage processes, prominently involving programmed cell death (PCD). Although apoptosis and necroptosis have been extensively characterized, the role of oncosis in SCI remains inadequately understood. In this study, we examined the expression dynamics and cellular localization of oncosis-related genes (ORGs) following SCI. We conducted an analysis of bulk RNA-seq data to identify differentially expressed ORGs at five distinct time points post-injury. Six candidate genes (Trp53, Casp3, Jun, Tmem123, Chmp6, Map2) were identified based on their temporal expression patterns. Single-cell RNA sequencing and spatial transcriptomics revealed specific cell-type specificity and lesion-centered spatial enrichment of these genes. Trp53 and Casp3 were found to be rapidly upregulated in neurons and microglia, whereas Tmem123 exhibited a progressive downregulation. Jun emonstrated biphasic activation in astrocytes and oligodendrocytes. In vitro experiments using LPS-treated PC12 cells corroborated key expression trends, with transmission electron microscopy (TEM) confirming the morphological characteristics of oncosis. In vivo, quantitative reverse transcription PCR (qRT-PCR) qRT-PCR and immunofluorescence analyses in a rat SCI model further validated the altered expression of these genes. Significantly, a reduction in Map2 and an elevation in Chmp6 were associated with cytoskeletal collapse and plasma membrane rupture, respectively. Together, our findings provide the first spatiotemporal mapping of oncotic gene regulation following SCI and identify potential targets for therapeutic intervention.